ESTIMASI PENYESUAIAN LIKUIDITAS TERHADAP VALUE AT RISK DARI DATA HISTORIS - Pratiwi, Noviana (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
Risk is often associated with volatility or deviation of investment return, investor required measure of risk to managing risk. Value at Risk (VAR) is a risk measurement techniques and considered the standard method of measuring risk. In portfolio, VaR is defined as the estimated of maximum loss will be experienced by a portfolio at a spesific time period with a certain confidence level. There are three main methods to calculate the VaR i.e. variance-covariance , historical simulation and monte carlo simulation method. Capital market are not perfected liquid, but VaR model is usually asumsed to be liquid market. Whereas liquidity of market should be considered in capital market due to be optimally role in supporting economic growh, the market must be liquid. Incorporation of liquidity risk into VaR model is called Liquidity adjuated Value at Risk (LVaR). In our work, LVaR is estimated for highly liquid and less liquid portfolio.